2006
DOI: 10.1029/2006ja011608
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric energy budget during huge geomagnetic activity using Cluster and ground‐based data

Abstract: [1] The Cluster spacecraft crossed the magnetopause at the duskward flank of the tail while the European Incoherent Scatter (EISCAT) radars and magnetometers observed the ionosphere during a sequence of intense substorm-like geomagnetic activity in October 2003. We attempt to estimate the local and global energy flow from the magnetosheath into the magnetotail and the ionosphere under these extreme conditions. We make for the first time direct observational estimates of the local solar wind power input using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 48 publications
2
47
1
Order By: Relevance
“…They found that in the simulation, the dayside load indeed appears adjacent to the reconnection region, while the generators are located behind the cusps in the tail lobes. Rosenqvist et al (2006) presented a method to investigate energy conversion using Cluster observations, and later the method was applied to both the load and generator cases (Rosenqvist et al, 2008). The most recent step using this methodology was to characterize the load-generator process systematically in a small data set using Cluster observations .…”
Section: Palmroth Et Al: Imf B Y and Tilt Dependence Of Energy Trmentioning
confidence: 99%
“…They found that in the simulation, the dayside load indeed appears adjacent to the reconnection region, while the generators are located behind the cusps in the tail lobes. Rosenqvist et al (2006) presented a method to investigate energy conversion using Cluster observations, and later the method was applied to both the load and generator cases (Rosenqvist et al, 2008). The most recent step using this methodology was to characterize the load-generator process systematically in a small data set using Cluster observations .…”
Section: Palmroth Et Al: Imf B Y and Tilt Dependence Of Energy Trmentioning
confidence: 99%
“…To our knowledge, the first experimental investigations of generator regions in the plasma sheet were presented in Marghitu et al (2006); Hamrin et al (2006). During a very strong geomagnetic activity a clear generator was identified at the magnetopause flank of the tail (Rosenqvist et al, 2006). The generators were identified as concentrated regions with negative power densities as obtained by Cluster.…”
Section: Introductionmentioning
confidence: 99%
“…A popular notion is hence that the aurora is powered by the solar wind. Indeed, an open magnetopause at a few R E tailward of the dawndusk meridian has been observed to act like a generator with a significant component of the magnetic tension directed against the solar wind flow, thus producing Poynting flux pointing into the magnetotail [Rosenqvist et al, 2006]. According to Rosenqvist et al [2006], estimates of the global Joule heating in the Earth's upper atmosphere and ionosphere during an intense storm amounted to roughly 35% of the power extracted from the solar wind at the magnetopause.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an open magnetopause at a few R E tailward of the dawndusk meridian has been observed to act like a generator with a significant component of the magnetic tension directed against the solar wind flow, thus producing Poynting flux pointing into the magnetotail [Rosenqvist et al, 2006]. According to Rosenqvist et al [2006], estimates of the global Joule heating in the Earth's upper atmosphere and ionosphere during an intense storm amounted to roughly 35% of the power extracted from the solar wind at the magnetopause. However, under normal circumstances we can expect that a considerable fraction of the electromagnetic power dissipated in the ionosphere is not directly generated at the magnetopause, since nightside auroral field lines on the equatorward edge of the oval, and at least up into the central part, map from the ionosphere rather into the tail region (specifically the plasma sheet).…”
Section: Introductionmentioning
confidence: 99%